Electronic cigarettes and public health awareness: a cross-sectional analysis of Google search inquiries. Issue 4 (18th June 2021) - Lester, Drew; Torgerson, Trevor; Eyabi, Jorgen; Wayant, Cole; Vassar, Matt
Abstract: The number of American adults who use electronic nicotine delivery systems (ENDS) increased by 3 million people in 2018, up 38.3% from 8.1 to 11.2 million. Search data for ENDS were analyzed against relevant traits including state longitude, tobacco tax rate and national tobacco program funding. Searches increased 88% (95% CI, 70–100) over the last 5 years and peaked on 8 September 2019, after the CDC issued a warning about the link between ENDS and high-profile lung damage cases. Searches aimed at buying ENDS subsequently dropped 25% (95% CI, 20.1–29.6), while health-related ENDS searches spiked to their all-time high, increasing 22% (95% CI, −6 to 55) compared with the first half of 2019. ENDS searches are now more concentrated than 5 years ago, reversing the trend of the early 2010s, likely because certain states have passed laws to curb the use of ENDS. The public prefers searching for 'vaping' over 'e-cigarette' in a phenomenon similar to 'high fructose corn syrup' versus 'sugar'. Consequently, public policy discussions and public education campaigns need to use 'vaping' terms, and more states should enact policies that are strongly associated with lower ENDS usage, many of which we identify.